2022
DOI: 10.3389/fpsyt.2022.1004318
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and related factors of depressive symptoms among HIV/AIDS in Ningbo, China: A cross-sectional study

Abstract: BackgroundDepressive symptoms were common among HIV/AIDS patients. Previous studies had shown that HIV-infected patients were twice as likely to be diagnosed with depression as the general population. However, only few studies have explored the prevalence and related factors of depressive symptoms among HIV/AIDS in China.Materials and methodsA cross-sectional study was conducted to study the prevalence of depressive symptoms among HIV/AIDS from January to December 2021 through the database of HIV/AIDS antiretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
4
1
1
Order By: Relevance
“…Higher total scores indicate more severe depressive symptoms. The PHQ-9 has demonstrated acceptable psychometric properties in the PLWH population [ 22 , 23 ], and the questionnaire is widely used in studies of Chinese PLWHs [ 20 , 24 ]. In the present study, the Cronbach’s α was 0.92.…”
Section: Methodsmentioning
confidence: 99%
“…Higher total scores indicate more severe depressive symptoms. The PHQ-9 has demonstrated acceptable psychometric properties in the PLWH population [ 22 , 23 ], and the questionnaire is widely used in studies of Chinese PLWHs [ 20 , 24 ]. In the present study, the Cronbach’s α was 0.92.…”
Section: Methodsmentioning
confidence: 99%
“…With longer ART initiation duration and experiencing the benefits of ART drugs, HIV patients may feel more normal regarding their disease status, have lower stress levels, and have decreased depressive symptoms. However, previous studies conducted in China, Bhutan, Ethiopia, and Cameroon [ 9 , 22 , 32 , 39 ] did not show any association. This could be because of the different cutoff points used for the duration of ART initiation.…”
Section: Discussionmentioning
confidence: 62%
“…Although Nepal has made substantial progress in its HIV prevention program by reducing the HIV incidence per 1000 population from 0.08% in 2010 to 0.02 in 2021 and increasing the number of ART sites from 2 in 2004 to 84 in 2022 [ 8 ], the mental health dimension of people living with HIV (PLHIV) often goes unnoticed and unaddressed. The global prevalence of depression among PLHIV ranges from 6.73% to 89.9% [ 9 , 10 ]. A recent meta-analysis study revealed the pooled prevalence of depression in PLHIV to be 31%, with the highest prevalence of 40% in the Southeast Asia region [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Entre ellos, el 71,5 % fue del sexo masculino; 86,1 % fue soltero; y el 25 % tenía secundaria completa. Resultados similares fueron obtenidos en otras investigaciones (8,22,23). Sin embargo, Olatayo et al (24) obtuvieron resultados diferentes en una muestra de pacientes con VIH de Nigeria, ya que asignaron un mayor porcentaje para mujeres (73,8 %), estado civil casado (76,2 %) y nivel de educación superior (58,7 %).…”
Section: Resultados Principalesunclassified